Analysis of the Job Satisfaction and Motivation on Employee Performance in the Rafflesia Hospitality Industry - Ihtiarna, Lampar; Astuti, Winda Dwi (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2025)
This study investigates the influence of job satisfaction and motivation on employee performance in the hospitality industry, with a focus on hotels in Rafflesia. Employees play a crucial role in delivering high-quality services and ensuring operational success. Using a survey-based quantitative approach, data were collected from hotel employees through questionnaires and analyzed using multiple linear regression. The results indicate that job satisfaction and motivation significantly impact employee performance. Intrinsic factors such as achievement, recognition, and responsibility, as proposed by Herzberg’s theory, as well as the fulfillment of needs according to Maslow’s hierarchy, contribute substantially to performance enhancement. These findings highlight the need for hotel management to develop strategies that enhance job satisfaction and motivation to optimize performance. Practical recommendations include continuous training programs, clear career development paths, and an effective reward system. By improving these factors, hotels can ensure higher employee commitment, better service quality, and improved overall organizational performance.